Terahertz GaAs/AlAs quantum-cascade lasers - Schrottke, Lutz (2016)
We have realized GaAs/AlAs quantum-cascade lasers operating at 4.75 THz exhibiting more than three times higher wall plug efficiencies than GaAs/Al0.25Ga0.75As lasers with an almost identical design. At the same time, the threshold current density at 10 K is reduced from about 350 A/cm2 for the GaAs/Al0.25Ga0.75As laser to about 120 A/cm2 for the GaAs/AlAs laser. Substituting AlAs for Al0.25Ga0.75As barriers leads to a larger energy separation between the subbands reducing the probability for leakage currents through parasitic states and for reabsorption of the laser light. The higher barriers allow for a shift of the quasi-continuum of states to much higher energies. The use of a binary barrier material may also reduce detrimental effects due to the expected composition fluctuations in ternary alloys.